PERAN GURU SEBAGAI MOTIVASI BELAJAR SISWA KELAS VII PADA MATA PELAJARAN AQIDAH DI SMP SCIENCE QUR’AN AL-IRSYAD JEMBER - Chusnul Salsabila; Sofyan Rofi; Badrut Tamami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of teachers in increasing the learning motivation of grade VII students in the subject of Faith at Al-Irsyad Science Junior High School Al-Irsyad Jember and identify the elements that support and hinder it. This type of research is qualitative descriptive. Data was collected through observation, interviews, and document collection. The data analysis method uses the qualitative analysis approach proposed by Creswell. The findings of the study show that teachers have carried out various main functions comprehensively, namely as role models, discipline cultivators, encouragers, movers, educators, examples, and liaison. The main supporting factor is the presence of school facilities such as LCD projectors and laptops. Meanwhile, the inhibiting factors consist of a lack of variety of learning media, limited time allocated to learning, and less focused student attention during learning activities.